NGO and Community Empowerment Based on Local Wisdom (a Case Study of Spedagi NGO in Temanggung, Central Java, 2018-2019) - Dian Eka Rahmawati; Dwi Woro Astuti (Universitas Muhammadiyah Yogyakarta, 2019)
Community empowerment is an effort to develop community skills through various activities by utilizing the potential of existing resources so that it has a positive impact on the socio-economic activities of the community. One significant role in community empowerment is the Non-Governmental Organization (NGO). This study aims to analyze the role of the NGO Spedagi in empowering rural communities based on local wisdom through the Papringan Market activity in Temanggung, Central Java.This study used a qualitative method. The researchers collected the data through observation, documentation, and interview techniques. The observation was examining various activities in Spedagi NGOs and the community, as well as the condition of the Papringan Market, was the observation. The researchers collected data for documentation from several types of literature, documents, websites, and official social media. The NGO's manager, the village leaders, the community, and Papringan Market traders were the parts of interviews. The results of this study found two purposes of the NGO Spedagi in empowering communities based on local wisdom through the Papringan Market. They were political and non-political purposes. The political role could be seen from the efforts to strengthen the capacity and articulation of community interests to increase community bargaining to influence village government policies while the non-political role could be seen from the efforts of the NGO Spedagi along with the local community to carry out physical development, economic empowerment, and social empowerment that lead to sustainability by utilizing the local potential.